NGS-analysis to the rescue: dual checkpoint inhibition in metastatic osteosarcoma – a case report and review of the literature. Issue 2 (4th March 2021) - Nuytemans, Laure; Sys, Gwen; Creytens, David; Lapeire, Lore
ABSTRACT: Background : The prognosis and treatment of metastatic osteosarcoma have not changed in the last decades and the responses to chemotherapy in this setting are disappointing. In the past years, immunotherapy has found its place in the treatment of different tumor types. Its role in the treatment of sarcomas, and in particular osteosarcoma, is less clear. Next-generation sequencing (NGS) can help identify patients who could benefit from immunotherapy. Methods: Single case study and review of the literature Case summary and intervention : We discuss a case of a 26-year-old man with a metastatic osteosarcoma not responsive to several lines of standard chemotherapy. NGS-analysis of resected tumor tissue revealed amplification of PD-L1 and PD-L2, which is associated in literature with response to anti-PD-1/PD-L1 blockade in other tumor types and in osteosarcoma mouse models. Treatment of our patient with the combination of an anti-PD-1 antibody (Nivolumab) and an anti-CTLA4 antibody (Ipilimumab) showed a stabilization of life-threatening retrocardiac tumoral masses that had previous significantly progressed despite radiotherapy, while one bone lesion in the right os ilium was growing and needed treatment with concomitant radiotherapy. Conclusion: To our knowledge, this is the first case report of a metastasized osteosarcoma patient with no further standard treatment options being treated with dual checkpoint inhibition. A complete stabilization of life-threatening retrocardiac lesions could be achieved and with the addition of radiotherapy to a growing bone lesion, the patient is still doing well. NGS-analysis can help identify druggable targets in patients with rare tumors with limited treatment options. Abbreviations: PD-L1: Programmed death-ligand 1; anti-PD-L1: anti-programmed death-ligand 1; PD-1: programmed cell death protein 1; anti-PD-1: anti-programmed cell death protein 1; anti-CTLA4: anti-cytotoxic T-lymphocyte-associated protein 4; AUC: area under the curve; NGS: next-generation sequencing; Gy: Gray; CT scan: computed tomography scan; RCC: renal cell carcinoma; IHC: immunohistochemistry; TMB: tumor mutational burden; NSCLC: Non-small cell lung cancer.